Réponses

2014-05-28T13:14:22+02:00
Exercice 1 : Calculer chaque expression. On donnera le résultat sous forme d'une fraction la plus simple possible

A = 4/3 - 1
      7/6 - 2
A = 4/3 - 1 x 3 /1 x 3
      7/6 - 2 x 6 / 1 x 6
A = 4/3 - 3/3
     7/6 - 12/6
A = 1/3 : - 5/6
A = 1/3 x - 6/5
A = - 6/15
A = 3 x - 2 / 3 x 5
A = - 2/5

B = 2/3 + 1/2
     17/9 - 1/3
B = 2 x 2 / 3 x 2 + 1 x 3 / 2 x 3
         17/9 - 1 x 3 / 3 x 3
B = 4/6 + 3/6
     17/9 - 3/9
B = 7/6 : 14/9
B = 7/6 x 9/14
B = 63/84
B = 21 x 3 / 21 x 4
B = 3/4

C = (2 - 11/9) x 1/2
                          5
C = (2 x 9 / 1 x 9 - 11/9) x 1/2
                                          5
C = (18/9 - 11/9) x 1/2
                               5
C = 7/9 x 1/2 : 5/1
C = 7/18 x 1/5
C = 7/90
Meilleure réponse !
2014-05-28T13:16:27+02:00
A=(4/3-1*3/3)/7/6-2*6/6
A=(4-3/3)/7-12/6
A=(1/3)/(-5/6)=1/3*(-6/5)=-6/15=-2/5

B=(2*2/3*2)+(1*3/2*3)/(17/9)-(1*3/3*3)=(4/6+3/6)/(17/9-3/9)=(7/6)/(14/9)=7/6*9/14=63/84=3/4

c=(2*9/9-11/9)*1/-2/5=(18-11/9)*-5/2=7/9*(-5/2)=-35/18